Analysis of Analisis Eksistensi Arsitektur Restoratif Pada Rumah Retret Girisonta - Violleta Adinda Putri; Dyah Titisari Widyastuti (Arsir: Jurnal Arsitektur, 2026)
Green areas in Central Java have experienced significant changes, known as the gradual reduction of green urban areas. The changes that have happened rapidly are impacting retreat houses that were previously located in secluded areas, are now nearing the highway and the residential areas. This research explores further about the existence of restorative architecture in Girisonta Retreat House, Central Java. Using a qualitative-descriptive approach, the research combines field observation, photographic documentation, and questionnaires based on Kaplan’s theory about restorative environment to the retreat participants. The findings reveal that Girisonta Retreat House is still able to provide restorative effects despite experiencing the impact of urban development, which resulting the retreat house to be located close to highways and residential areas. This research contributes to the discourse on healing architecture and shows how important of a space or environment in effecting human psychology.